2017
DOI: 10.15448/1980-6108.2017.2.25857
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with type 2 diabetes mellitus treated with metformin

Abstract: AIMS: To evaluate oxidative stress parameters in patients with type 2 diabetes mellitus treated with metformin, relating these values to its side effects, plasma levels, glycemic control, diabetic complications, lipid profile, and the influence of pharmacotherapeutic follow-up. METHODS: Patients with type 2 diabetes mellitus, on metformin and in pharmacotherapeutic follow-up for four months, were evaluated. The pharmacotherapeutic follow-up consisted in providing information and answering patients' questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The HbA1c% shows the negatively correlated to superoxide dismutase (SOD) but positively correlated to malondialdehyde (MDA) but it was not significant. Other authors also reported same thing as our study shows the positive correlation between glycemic control parameters and MDA in DM patients [17,18,29,30] due to excessive accumulation of lipid peroxidation products. Our study revealed that SOD activity was decreased as in case of T-2DM with complication than without complication and control group due to auto-oxidation of glucose and more H2O2 production, but it was reverse in other reported studies due to increased protein glycation, which leads to reduced vascular concentrations of SOD-3 in relation to intracellular SOD-1 activity is also decreased, resulting into an increased superoxide production [22,31,32].…”
Section: Discussionsupporting
confidence: 88%
“…The HbA1c% shows the negatively correlated to superoxide dismutase (SOD) but positively correlated to malondialdehyde (MDA) but it was not significant. Other authors also reported same thing as our study shows the positive correlation between glycemic control parameters and MDA in DM patients [17,18,29,30] due to excessive accumulation of lipid peroxidation products. Our study revealed that SOD activity was decreased as in case of T-2DM with complication than without complication and control group due to auto-oxidation of glucose and more H2O2 production, but it was reverse in other reported studies due to increased protein glycation, which leads to reduced vascular concentrations of SOD-3 in relation to intracellular SOD-1 activity is also decreased, resulting into an increased superoxide production [22,31,32].…”
Section: Discussionsupporting
confidence: 88%
“…Another protective role is to reduce the concentration of insulin, thus diminishing the hyperinsulinism associated stress [19,53]. In patients with poor glycaemic control and diabetic complications, with documented high OS levels, metformin could prevent further development of complications [17,60,83]. Liraglutide is a glucagon like peptide-1 receptor agonist that improves glucose-dependent insulin secretion capacity and beta-cell function [77].…”
Section: Antidiabetic Medications With a Potential Antioxidant Rolementioning
confidence: 99%
“…1 The management of DM involves pharmacological (use of oral hypoglycemic drugs and/or insulin) and non-pharmacological approaches. 2 The oral hypoglycemic drugs include Sulfonylureas, Biguanides and Thiazolidinediones. The Thiazolidinediones like Pioglitazone are selective ligands for peroxisome proliferator-activated receptors (PPAR-γ).…”
Section: Introductionmentioning
confidence: 99%